2017
DOI: 10.1126/sciimmunol.aag0192
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomics of human CD8 T cell differentiation and aging

Abstract: The efficacy of the adaptive immune response declines dramatically with age, but the cell-intrinsic mechanisms driving immune aging in humans remain poorly understood. Immune aging is characterized by a loss of self-renewing naïve cells and the accumulation of differentiated but dysfunctional cells within the CD8 T cell compartment. Using ATAC-seq, we inferred the transcription factor binding activities correlated with naive and central and effector memory CD8 T cell states in young adults. Integrating our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
171
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 195 publications
(198 citation statements)
references
References 54 publications
19
171
1
Order By: Relevance
“…Changes in CD8 + T cell transcriptomes are largely due to increased frequencies of effector CD8 + T cells (Cao et al, 2010). A separate analysis of CD28 + and CD28 − CD8 + T cells in young and old individuals were consistent with the model that old CD28 + CD8 + T cells were more differentiated (Lazuardi et al, 2009) as also suggested by the epigenetic studies of CD8 + T cell subsets (Moskowitz et al, 2017). Because a major feature of T cell aging appears to be the initiation of differentiation steps, the analysis of individual T cell subsets in functional studies is important.…”
Section: Age-associated Defects In T Cell Activationsupporting
confidence: 87%
See 3 more Smart Citations
“…Changes in CD8 + T cell transcriptomes are largely due to increased frequencies of effector CD8 + T cells (Cao et al, 2010). A separate analysis of CD28 + and CD28 − CD8 + T cells in young and old individuals were consistent with the model that old CD28 + CD8 + T cells were more differentiated (Lazuardi et al, 2009) as also suggested by the epigenetic studies of CD8 + T cell subsets (Moskowitz et al, 2017). Because a major feature of T cell aging appears to be the initiation of differentiation steps, the analysis of individual T cell subsets in functional studies is important.…”
Section: Age-associated Defects In T Cell Activationsupporting
confidence: 87%
“…Repression of PGC1α, an important cofactor of NRF1 activity, is an early event in T cell exhaustion, indicating a mechanistic overlap between T cell aging and exhaustion (Bengsch et al, 2016). However, CD8 + CD45RO + CCR7 − effector memory T cells from older individuals show only few differences in terms of chromatin accessibility compared to young effector memory T cells, and they lack the epigenetic signatures of exhausted T cells (Moskowitz et al, 2017; Sen et al, 2016). This observation suggests that T cell aging mainly affects naive and central memory CD8 + T cells, possible employing pathways similar to exhaustion.…”
Section: Age and T Cell Exhaustionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to earlier predictions, the size and diversity of the human CD4 + T cell repertoire in older individuals is sufficient to respond to a diverse set of antigenic peptides (Qi et al, 2014). The CD8 + T cell compartment is more affected by age, both in size and composition as well as in function and chromatin structure (Briceño et al, 2016; Czesnikiewicz-Guzik et al, 2008; Moskowitz et al, 2017; Nikolich-Zugich et al, 2012). Defects in T cell activation because of reduced dendritic cell function or T cell receptor (TCR) signaling have been described (Li et al, 2012; Montgomery and Shaw, 2015) and may be overcome by adjuvanted vaccines or increasing the antigen dose (DiazGranados et al, 2014).…”
Section: Introductionmentioning
confidence: 99%